FAMILY KNOWLEDGE ABOUT CARE FOR DIABETES MELLITUS PATIENTS IN THE TRENGGALEK COMMUNITY HEALTH CENTER WORK AREA - Zevina Dwi Andini; Elok Yulidaningsih; Rahayu Niningasih; Edi Yuswantoro (SYNTHESIS Global Health Journal, 2025)
Background. Diabetes Mellitus (DM) is a chronic metabolic disease that imposes significant burdens on health care and the socio-economic aspects of communities. Family involvement as primary caregivers is crucial for effective DM management through activities such as diet regulation, medication reminders, and blood sugar monitoring. The family's knowledge of including its definition, causes, symptoms, and management, is vital for patient recovery. Misunderstandings about care practices can lead to poor glycemic control and hasten complications, primarily due to inadequate education and limited access to primary care. The purpose of this study was to determine family knowledge about care for patients with Diabetes Mellitus. Research Method. The research design used in this study was descriptive quantitative, with one variable, namely family knowledge about care for patients with diabetes mellitus. The sampling technique used was purposive sampling with a sample size of 24 people. The study was conducted from March 2, 2025, to March 22, 2025, in the Trenggalek Community Health Center work area, in Sambirejo Village. Findings. The results showed that family knowledge about care for DM patients in the Trenggalek Community Health Center work area in 2025, most (63%, 15 respondents) had good knowledge. Conclusion. Family knowledge about care for patients with diabetes mellitus, namely by strengthening family education programs at the community health center level, developing educational materials that are easy to understand, and practical coaching programs for the use of glucometers.